A review of Synegiodes Swinhoe, 1892 (Lepidoptera: Geometridae), with description of two new species - Cui, Le; Jiang, Nan; Stüning, Dieter; Han, Hongxiang (Zootaxa, 2018)
The genus Synegiodes Swinhoe, 1892 is reviewed and redescribed, S. sanguinaria (Moore, 1868) is formally fixed as type-species according to the provisions of the International Code of Zoological Nomenclature. Seven species, including S. brunnearia (Leech, 1897), are presently recognized as members of this genus and two new species from China and N. Vietnam, S. expansus sp. nov. and S. elasmlatus sp. nov., are described herein. The original specific status of S. histrionaria ornata (Bastelberger, 1909) is restored. The systematic position of S. brunnearia is discussed. Diagnoses for all the species are provided and illustrations of external features and genitalia are presented.